Photo-treatment of palm oil mills effluent (pome) over cu/tio2 photocatalyst - Ng, Kim Hoong (2013)
The current work reports the use of titania based photocatalysts for the photo-treatment of palm oil mill effluent collected from Felda Lepar Hilir 3, a local source. Different metal loadings of copper viz. 2wt%, 5wt%, 10wt%, 15wt%, 20wt% and 25wt% were doped onto titania employing wet impregnation method. The synthesized catalysts were subjected to physicochemical characterization. Gas pycnometer density measurements revealed that the actual density of catalysts were lower than theoretical density due to the porous structure as proven by the subsequent liquid N2 physisorption. In addition, X-ray diffraction pattern showed formation of CuO with crystallite size ranging from 41.8 to 49.1 nm upon calcination. Significantly, liquid N2 physisorption showed that the BET specific surface area of catalysts prepared decreased with wt% of Cu probably due to pore blockage Moreover, 5wt% Cu/TiO2 exhibits the largest pore volume, which is 0.049 cm3/g for both adsorption and desorption volume. In the term of pore size, 20wt% of Cu/TiO2 has the largest adsorption pore size, which is 23.39 nm while 5wt% of Cu/TiO2 has the largest desorption pore size, which is 19.83 nm. Based on the UV-irradiated photoreaction results, 20wt% Cu/TiO2 yielded the highest organic degradability (conversion) among all the synthesized catalysts. Overall, 27.0% conversion was achieved within 1 h of photoreaction. Based on the integral method, it seems that the POME photo-reaction followed the 2nd-order reaction. Moreover, 20 wt% Cu/TiO2 exhibited the highest specific reaction constant at 2.60×10-5 (ppm.min)-1. Besides, an optimum catalyst loading were also discovered in current project. For 20wt% Cu/TiO2, the optimum catalyst loading is 0.83g/L of POME solution. Finally, a longevity test was conducted and it was found that more than 40% of the organic contaminant was decomposed after 7 h of UV-irradiation. Moreover, CO and CO2 were detected in the gas products from GC analysis. As conclusion, phototreatment for POME shows positive results in current project and is suitable to replace the existing traditional POME method for better efficiency